(untitled) (The Strategic Review for Southern Africa, 2020)
In recent years, Russian President Vladimir Putin increasingly places a high premium on re-building Russia’s global influence, which includes a boosting of Russia’s relations with the African continent. This coincides with Putin’s position that the strengthening of ties with African states is a Russian foreign policy priority. Moreover, there is little doubt that much of Moscow’s new involvement in Africa relates to Putin’s desire to revive his country’s great-power status. The main research question is: What is behind Moscow’s renewed push into the continent? Three areas of Russia-Africa relations of special importance are suggested in this article. Firstly, much of Russia’s focus on the African continent centres on energy diplomacy. Secondly, Russia is the second largest exporter of arms globally after the United States, and Moscow is a major supplier of weapons and military aid to Africa. Thirdly, the continent is rich in mineral wealth, and Moscow has an economic interest in mineral riches in Africa. This article argues the above-mentioned issues are the main drivers underlying Russia’s renewed strategic engagement with the African continent. The article further reflects on whether Russia’s foreign policy successes in Africa have been overblown, or whether Russia’s renewed engagement with Africa is actually of considerable significance in the global context and from an African point of view.